1996
DOI: 10.1902/jop.1996.67.6.577
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a 2‐Phase Oil:Water Mouthrinse in Controlling Oral Malodor, Gingivitis, and Plaque

Abstract: The purpose of the study was to examine the anti‐malodor, anti‐gingivitis, and plaque reducing properties of a 2 phase oil:water mouthrinse compared with a control mouthrinse. Fifty subjects rinsed with one of the two rinses for 30 seconds twice a day over 6 weeks, while continuing their normal oral hygiene habits. Measurements were made at time zero (prior to beginning the rinsing regimen), and ≥ 9 hours following rinsing, at intervals of 1, 3, and 6 weeks. Malodor of whole mouth, as well as tongue dorsum ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 23 publications
2
64
0
10
Order By: Relevance
“…The inhibition of VSCs also suppresses degradation of the cellular components of saliva 11) . This in vitro study compared the rates of inhibition of VSCs using either zinc chloride alone, or a combination of zinc chloride and citric acid.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of VSCs also suppresses degradation of the cellular components of saliva 11) . This in vitro study compared the rates of inhibition of VSCs using either zinc chloride alone, or a combination of zinc chloride and citric acid.…”
Section: Discussionmentioning
confidence: 99%
“…Adding olive oil to the CH core provides a layer of protection from the aqueous environment. Studies have shown that while aqueous solutions of CH rapidly increased the pH in tissues, oily CH suspensions produced a long-lasting gradual pH increase without irritation and were more effective than water-based vehicles at reducing microbial populations (Kozlovsky et al, 1996;Kasaj et al, 2006). A review of CH-delivery vehicles indicated that a relatively fast initial ion release is important after endodontic treatment (Fava and Saunders, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time when the air in the mouth is collected, the patient is asked to breathe through the nose. Sulfur components in the breath are detected by electrochemical reaction (29,38,39). This method is reproducible and easy to use.…”
Section: Sulfide Monitoringmentioning
confidence: 99%